1997
DOI: 10.2190/8l57-yt6l-xqcl-8ddp
|View full text |Cite
|
Sign up to set email alerts
|

Respect Redefined: Focus Group Insights from Singapore

Abstract: This article re-examines the meaning of the concept of respect within the context of a fast modernizing Asian multicultural society-Singapore. Two key findings emerge. First, the meaning of respect both from the perspective of the aged and the middle-aged generation has shifted from obedience to courteous behavior. Second, in the majority of focus groups members concurred that the degree of respect accorded to elders has in general decreased. The focus group methodology was used in this research. Bearing in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…A third study by Mehta (1997), which is most relevant to our own research, used qualitative methods to examine respect for the elderly in Singapore. Her research was based on data from focus group interviews with the elderly and adult children, in which participants compared current and past respect for the elderly.…”
mentioning
confidence: 99%
“…A third study by Mehta (1997), which is most relevant to our own research, used qualitative methods to examine respect for the elderly in Singapore. Her research was based on data from focus group interviews with the elderly and adult children, in which participants compared current and past respect for the elderly.…”
mentioning
confidence: 99%
“…First, older females were not significantly underrepresented in comparison with their male counterparts (by both measures of counts and screen time), whereas a consistent finding reported by U.S. investigators is that older females were seriously underrepresented on television in comparison with older males (Aronoff, 1974;Gerbner et al, 1980;Harwood & Anderson, 2002;Vernon et al, 1990). These findings are somewhat surprising and unexpected, given the commonly held cultural norms that older women in Chinese society occupy a lower status than older men (Mehta, 1997). One possible explanation is that the visibility on television may be a combined effect of the materialistic nature of a society and the program and target audience characteristics.…”
mentioning
confidence: 80%
“…For instance, Vernon et al (1990) reported that older characters were more likely to be associated with favorable stereotype traits than unfavorable ones, hence suggesting a more positive picture about age stereotypical images on prime-time television. Saengtienchai, 1999;Mehta, 1997). For example, Mehta (1997) examined young people's attitudes toward elder respect and concluded that elder respect is shifting from obedience and subservience to courtesy and kindness.…”
mentioning
confidence: 99%
See 2 more Smart Citations